Perancangan Sistem Informasi Perekrutan Karyawan Berbasis Web (Studi Kasus PT. Transdata Satkomindo Medan) - Chairul Rizal; Supiyandi; Dian Sanjaya (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
Web-Based Employee Recruitment Information System or e-Recruitment can be used as a solution in handling the employee recruitment process in a company. With a web-based employee recruitment information system or e-recruitment, companies can choose the right employees for their company. In addition, the company can also process address data in the database so that applicant data does not accumulate in the filing cabinet. In this study, the author discusses how to design a web-based employee recruitment information system. The system development methodology used is the System Development Life Cycle (SDLC) waterfall model which includes the stages of system planning, system analysis, system design and system implementation. The system is built using the PHP programming language, database server with MySQL. The result to be achieved from this research is that a web-based employee recruitment information system is expected to assist the company's HRD in the employee recruitment process and make it easier for managers to view employee acceptance reports.